GAMBARAN FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT TERHADAP VAKSIN COVID-19 DI DESA MANGGISSARI KECAMATAN PEKUTATAN - Marangyana I Gede Bagus Indra; Yunita Ella; Yunita Sari Ni Kadek Dwi (Journal Pharmactive, 2023)
This study aims to describe the factors that influence people's interest in the Covid-19 vaccine in Manggissari Village, Pekutatan District. This type of research is a quantitative study using the Cross-Sectional method. The sampling technique in this study was Simple Random Sampling, the total sample population was 237 in Manggissari Village, Pekutatan District. The results obtained from the frequency distribution show that from a total sample of 237 it can be seen that as many as 23.2% of the respondents who have not been vaccinated, not yet fully vaccinated (27.4%) and have had complete vaccines (49.4%), the community still has mostly low knowledge (49.8%), lack of information about the covid-19 vaccine (15.6%), lack of support from family (49.4%) and the influence of the community environment mostly (46.4%) . Based on the research above, there are factors that influence public interest in the Covid-19 vaccine. This research is expected to increase high awareness of carrying out the Covid-19 vaccination.